2023
DOI: 10.3389/fpls.2023.1031426
|View full text |Cite
|
Sign up to set email alerts
|

Roles of type II H+-PPases and PPsPase1/PECP2 in early developmental stages and PPi homeostasis of Arabidopsis thaliana

Abstract: The regulation of intracellular pyrophosphate (PPi) level is crucial for proper morphogenesis across all taxonomic kingdoms. PPi is released as a byproduct from ~200 metabolic reactions, then hydrolyzed by either membrane-bound (H+-PPase) or soluble pyrophosphatases (PPases). In Arabidopsis, the loss of the vacuolar H+-PPase/FUGU5, a key enzyme in PPi homeostasis, results in delayed growth and a number of developmental defects, pointing to the importance of PPi homeostasis in plant morphogenesis. The Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Most interestingly, vpp5 grains consistently showed reduced chalk (Table 1). Accumulation of PPi, however, causes developmental defects (Tojo et al., 2023). Arabidopsis V‐PPase mutant fugu5 and the RNAi suppression lines display mild to severe growth retardation, which can be rescued by the exogenous supply of sucrose (Ferjani et al., 2011; Pizzio et al., 2015; Segami et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, vpp5 grains consistently showed reduced chalk (Table 1). Accumulation of PPi, however, causes developmental defects (Tojo et al., 2023). Arabidopsis V‐PPase mutant fugu5 and the RNAi suppression lines display mild to severe growth retardation, which can be rescued by the exogenous supply of sucrose (Ferjani et al., 2011; Pizzio et al., 2015; Segami et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This missense mutation (G800A in CDS) led to an amino acid substitution of glycine to aspartic acid (G267D in protein). G267 is predicted to be located close to the 6th transmembrane domain, and is conserved among AVP1, AVP2;1 and AVP2;2 ( Segami et al., 2010 ; Tojo et al., 2023 ). To examine if the mutant phenotype was because of its mutation in AVP2;1 , two T-DNA lines of AVP2;1 were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of this mutant variant into fugu5-3 rescued shoot growth as when native H + -PPase (AVP1) was introduced (Asaoka et al, 2016), thereby supporting that the hydrolytic role rather than proton pumping of AVP1, is essential for plant growth. On the other hand, Tojo et al (2023) has revealed the negligible contribution of PPi hydrolytic role of AVP2;1 in growth of A. thaliana seedling. This was done by phenotypic characterization of the AVP2;1 mutant, vhp2;1-1/avp2;1-1 (SAIL_512_B02) and fugu5-1vhp2;1-1 double mutant.…”
Section: Discussionmentioning
confidence: 99%